Socio-Economic Realities of Dalit Muslim Women in India During Covid-19 - Rimmi Datta; Jayanta Mete (UIN Sunan Gunung Djati Bandung, 2022)
Dalit women, especially Muslims in India, are seen to be present at a crucial moment when they must overcome three barriers at once: class, race, and masculinity. Muslim Dalit women have been victims of sexual assault in rural India. The disadvantages of Muslim Dalit women are among the most notable exceptions; their disadvantages are never part of the battle for women in India. However, bourgeois feminism did not advance all the real issues of Dalit women by setting the feminist agenda. The additional bias against Muslim Dalit women due to their gender and caste is evident in the numerous successes achieved by the human development metrics of this group. In all aspects of human growth, literacy, and survival, Muslim Dalit women are far worse off than Dalit men and non-Dalit women. This study aims to comprehend the larger connotations that connect Muslim Dalit women's social spaces to COVID-19. In conjunction with these social and political trends, the mistreatment of Muslim Dalit women is on the rise, as is subtle or extreme discrimination within Dalit households. Therefore this study uses a qualitative approach to address issues concerning Dalit women